2012
DOI: 10.1002/hipo.22005
|View full text |Cite
|
Sign up to set email alerts
|

Learning‐dependent plasticity of hippocampal CA1 pyramidal neuron postburst afterhyperpolarizations and increased excitability after inhibitory avoidance learning depend upon basolateral amygdala inputs

Abstract: Hippocampal pyramidal neurons in vitro exhibit transient learning-dependent reductions in the amplitude and duration of calcium-dependent postburst afterhyperpolarizations (AHPs), accompanied by other increases in excitability (i.e., increased firing rate, or reduced spike-frequency accommodation) after trace eyeblink conditioning or spatial learning, with a time-course appropriate to support consolidation of the learned tasks. Both these tasks require multiple days of training for acquisition. The hippocampus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 52 publications
5
32
0
Order By: Relevance
“…Different from the MWM test, the Passive Avoidance learning was shown to involve hippocampal in addition to the amygdala function because of having contextual features in addition to fearrelated factors [35][36][37]. Relatively few studies have used Passive Avoidance Test in the chronic mild stress models.…”
Section: Discussionmentioning
confidence: 95%
“…Different from the MWM test, the Passive Avoidance learning was shown to involve hippocampal in addition to the amygdala function because of having contextual features in addition to fearrelated factors [35][36][37]. Relatively few studies have used Passive Avoidance Test in the chronic mild stress models.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, a reduction of AHP has previously been demonstrated after 30-35 days of periodic enrichment in male rats [35]. In addition, a reduction of AHP due to learning has long been established [1,8,14,38,48]. Recently, Farmer and Thompson [14] have shown that a single exposure to a novel context is sufficient to decrease both mAHP and sAHP in CA1 pyramidal neurons.…”
Section: Possible Ionic Mechanisms Supporting the Modulation Of Excitmentioning
confidence: 95%
“…In addition, a reduction of AHP due to learning has long been established [1,8,14,38,48]. Recently, Farmer and Thompson [14] have shown that a single exposure to a novel context is sufficient to decrease both mAHP and sAHP in CA1 pyramidal neurons. Therefore, a common mechanism might increase cellular excitability through the modulation of AHP after learning and after an exposure to environment enrichment.…”
Section: Possible Ionic Mechanisms Supporting the Modulation Of Excitmentioning
confidence: 98%
“…Similarly, 24 h after acquisition of an IA task, in which a high-intensity footshock was paired with the dark compartment, hippocampal CA1 post-burst afterhyperpolarizations (AHPs) were significantly reduced, i.e. intrinsic excitability was enhanced (Farmer & Thompson, 2012), while immediate post-trial BLA lidocaine infusions blocked this learning-dependent plasticity in CA1 AHPs. Learning-dependent reductions in CA1 neuron AHPs are a reliable and highly replicable cellular mechanism expressed in hippocampus, with a time-course appropriate to support memory consolidation (Disterhoft & Oh, 2006;Farmer & Thompson, 2012;McKay, Mathews, Oliveira, & Disterhoft, 2009;Oh, Kuo, Wu, Sametsky, & Disterhoft, 2003;Oh, Oliveira, & Disterhoft, 2010;.…”
Section: Introductionmentioning
confidence: 98%